Seasonal variations in the life cycle and morphology of Anisops breddini (Hemiptera: Notonectidae). Issue 4 (2nd October 2021) - Memtombi Chanu, Chongtham; Gupta, Susmita; Gupta, Abhik
ABSTRACT: Studies on temperature-dependent phenology and morphology of insects facilitate examination of the consequences of temperature on their growth, development and population dynamics. The effects of seasonal changes on the life cycle and morphometry of Anisops breddini were studied by rearing eggs to adults under laboratory conditions during the wet and dry seasons. The average incubation period of eggs, developmental durations of instars I–V and total developmental time were significantly less at warm temperature (wet season) than in cold temperature (dry season). However, the hatching percentage was significantly higher at warm temperature than in cold temperature. Morphometric measurements of nymphs and adults were also significantly less at warm temperature than in cold temperature. Laboratory reared individuals during the wet season at warm temperature had faster development and produced smaller individuals as compared with the dry season. The developmental durations and body size of the experimental individuals were significantly negatively correlated with rearing temperature. The study further revealed that in warm temperature the developmental duration of the experimental individuals become shorter which in turn might increase the number of generations of this insect.